Genetic Editing with CRISPR Cas9: recent Biomedical and Biotechnological Applications - Fabián Andrés Garzón Posse; Angie Kathleen Pinilla Peña; Cesar Augusto Rivas Velásquez; María Camila Murillo Virgüez; Jorge Alberto Gutiérrez Méndez (Universitas Scientiarum)
The use of a novel and powerful technology that allows for the precise editing of the genetic material of various organisms is becoming widespread. This technology derives from bacterial and archaeal defense machinery and is called CRISPR Cas9. Unlike other gene editing tools that exclusively rely on proteins, CRISPR Cas9 utilizes interactions between the target DNA and an RNA sequence that guides the Cas9 enzyme to alter the structure of a target gene. Various genome locations can be edited thanks to the ease of programming different guide RNA sequences, facilitating its use and implementation. Furthermore, the non-active version of the Cas9 protein, guided by its corresponding RNA, can be utilized for visualization processes of genetic material or, more recently, for the regulation of the transcription process. Considering the recent advances and possibilities in biomedical and biotechnological research, we must understand that the exploration of this technology is just beginning, and its eventual applications will influence the world around us on multiple levels. In this review, we describe the biological foundations of the functioning of the Cas9 nuclease, together with selected applications of its use in editing and regulating specific sections of the genetic material of various organisms. We also discuss some bioethical issues surrounding this subject.